Optically Modulated Fluorescence Bioimaging: Visualizing Obscured Fluorophores in High Background - Hsiang, Jung-Cheng (American Chemical Society, 2014)
[Image: see text] Fluorescence microscopy and detection have become indispensible for understanding organization and dynamics in biological systems. Novel fluorophores with improved brightness, photostability, and biocompatibility continue to fuel further advances but often rely on having minimal background. The visualization of interactions in very high biological background, especially for proteins or bound complexes at very low copy numbers, remains a primary challenge. Instead of focusing on molecular brightness of fluorophores, we have adapted the principles of high-sensitivity absorption spectroscopy to improve the sensitivity and signal discrimination in fluorescence bioimaging. Utilizing very long wavelength transient absorptions of kinetically trapped dark states, we employ molecular modulation schemes that do not simultaneously modulate the background fluorescence. This improves the sensitivity and ease of implementation over high-energy photoswitch-based recovery schemes, as no internal dye reference or nanoparticle-based fluorophores are needed to separate the desired signals from background. In this Account, we describe the selection process for and identification of fluorophores that enable optically modulated fluorescence to decrease obscuring background. Differing from thermally stable photoswitches using higher-energy secondary lasers, coillumination at very low energies depopulates transient dark states, dynamically altering the fluorescence and giving characteristic modulation time scales for each modulatable emitter. This process is termed synchronously amplified fluorescence image recovery (SAFIRe) microscopy. By understanding and optically controlling the dye photophysics, we selectively modulate desired fluorophore signals independent of all autofluorescent background. This shifts the fluorescence of interest to unique detection frequencies with nearly shot-noise-limited detection, as no background signals are collected. Although the fluorescence brightness is improved slightly, SAFIRe yields up to 100-fold improved signal visibility by essentially removing obscuring, unmodulated background ( C. I. Richards; J. Am. Chem. Soc.2009, 131, 461919284790). While SAFIRe exhibits a wide, linear dynamic range, we have demonstrated single-molecule signal recovery buried within 200 nM obscuring dye. In addition to enabling signal recovery through background reduction, each dye exhibits a characteristic modulation frequency indicative of its photophysical dynamics. Thus, these characteristic time scales offer opportunities not only to expand the dimensionality of fluorescence imaging by using dark-state lifetimes but also to distinguish the dynamics of subpopulations on the basis of photophysical versus diffusional time scales, even within modulatable populations. The continued development of modulation for signal recovery and observation of biological dynamics holds great promise for studying a range of transient biological phenomena in natural environments. Through the development of a wide range of fluorescent proteins, organic dyes, and inorganic emitters that exhibit significant dark-state populations under steady-state illumination, we can drastically expand the applicability of fluorescence imaging to probe lower-abundance complexes and their dynamics.